Мінскі тафсір 1686 г. Вынікі апошніх даследаванняў - Тарэлка, Міхаіл (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The article talks about the oldest copy of the Polish translation of Koran made in Minsk by the Tatar (Muslim) interpreter Uriash ibn Ismail (Imam of Minsk) in the second half of the 17th century. The article consists of two parts devoted to the orthographic system of the manuscript and to the specific features of its language caused by the influence of the Belarusian and Arabic languages.